1970
DOI: 10.7577/rerm.2556
|View full text |Cite
|
Sign up to set email alerts
|

The linguistics in othering: Teacher educators’ talk about cultural diversity

Abstract: ‘Othering’ can be conceptually defined as the manner in which social group dichotomies are represented in language via binary oppositions of ‘us’ and ‘them’. The article aims to contribute to a methodological approach for differentiating the concept of othering in educational settings. We will introduce new ways of conceptualising othering based on findings from an empirical critical discourse analytical study of how teacher educators talk about the term ‘cultural diversity’. The study is based on transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Interview data is often taken to study discourse (Abell & Myers, 2008; Nikander, 2012), on societal processes, identity, language and culture (e.g. Hatoss, 2012; Nielsen et al, 2017). Particularly relevant here is the study of Nielsen et al (2017) that analyzed teacher educators’ discourses on cultural diversity and showed the dimensions through which Othering occurred.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interview data is often taken to study discourse (Abell & Myers, 2008; Nikander, 2012), on societal processes, identity, language and culture (e.g. Hatoss, 2012; Nielsen et al, 2017). Particularly relevant here is the study of Nielsen et al (2017) that analyzed teacher educators’ discourses on cultural diversity and showed the dimensions through which Othering occurred.…”
Section: Methodsmentioning
confidence: 99%
“…This is problematic for the contemporary composition of societies since, while a division line is drawn between nationals and non-nationals, „visible minorities remain invisible in the unambigous discursive divide of European and migrants” (El-Tayeb, 2011, p. xxi). Nielsen et al (2017) analyzed cultural Othering and found seven types of division lines: culture-nationality, social aspects, multilingualism, migration, nationality, visibility, and religion (p. 45). Therefore, Othering processes do not only occur between nationals and migrants, they are also broadly driven by the idea of (mis)recognizing people as ‘outsiders’ or ‘invisibles’ in a shared place (Ahmed, 2000; El-Tayeb, 2011; Hatoss, 2012).…”
Section: Theoretical Lens: Othering As a Societal Discoursementioning
confidence: 99%
See 1 more Smart Citation
“…The analysis followed a fourstep process inspired by Fosse et al (2018) and Nilsen et al (2017). The process was partly planned in advance and developed as the analytical process progressed.…”
Section: Analysis Proceduresmentioning
confidence: 99%
“…Implicit bias is defined as "attitudes or stereotypes that affect our understanding, actions, and decisions in an unconscious manner," and is a concept most often used to describe actions, beliefs, and behaviors towards people or social groups (Staats & Patton, 2013). As bias is a very human activity, it can be found in all places that humans are, including (but not limited to) classrooms (Nilsen, Fylkesnes, & Mausethagen, 2017), social media (Gendron, Welleford, Inker, & White., 2016), workplaces (Cook Ross, Inc., 2008), courtrooms (Goff, Eberhardt, Williams, & Jackson, 2008), newspapers (Lynott et al, 2019), and healthcare (Ashford, Brown, & Curtis., 2018). Implicit bias can relate to ways that we organize ourselves socially, for example race (Graham & Lowery, 2004), gender (Dervan, Zimmerman, Thompson, & Watson., 2019), age (Gendron et al, 2016), and culture (Nilsen et al, 2017).…”
Section: Language and Biasmentioning
confidence: 99%